2013
DOI: 10.5897/ijnm2013.0115
|View full text |Cite
|
Sign up to set email alerts
|

The partograph: A labour management tool or a midwifery record?

Abstract: A partograph is a graphical presentation of a woman's progress of labour. Once the woman has true signs of labour, the midwife initiates the use of the partograph to record her findings. The partograph was endorsed and modified by the World Health Organisation (WHO) between 1990 and 2000 to monitor the fetal and maternal wellbeing during the active stage of labour. Monitoring help the midwives and the mother in achieving spontaneous vaginal delivery with low risk of both morbidity and mortality. Furthermore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Similarly, a study in Rujumbura Health sub-district in Southern Western, Uganda found that the various health centers had sufficient numbers of the Partographs although their utilization was low [15]. However, other sites have documented unavailability as a problem for example in Central Ethiopia, Nigeria and South Africa [12, 18, 28]. In our study, the unavailability of Partograph may be due to the high patient numbers served by the hospital, and/or the adequacy of the hospital stationery supply system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in Rujumbura Health sub-district in Southern Western, Uganda found that the various health centers had sufficient numbers of the Partographs although their utilization was low [15]. However, other sites have documented unavailability as a problem for example in Central Ethiopia, Nigeria and South Africa [12, 18, 28]. In our study, the unavailability of Partograph may be due to the high patient numbers served by the hospital, and/or the adequacy of the hospital stationery supply system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the partograph is not used to the required standards even in settings where a printed partograph is available (Bedwell et al, 2017;Maphasha et al, 2017). A study conducted in South Africa (Mathibe-Neke et al, 2013) showed that most of the parameters recorded on a partograph were below average, ranging between 41% and 44%. In Uganda, a study to assess use of a partograph in Rukungiri district health centre showed that, although nearly 70% of deliveries had a partograph completed, fetal heart rate monitoring was performed in only 2% of the women (Ogwang et al, 2009).…”
mentioning
confidence: 99%
“…Thus, it can reduce the Maternal Mortality Rate (MMR). The first partograph was introduced by Friedman in 1950, then developed and redesigned by Philpott and Puri in 1971 by adding the concept of warning and action lines (Archa Prem 2013; Gitanjali, 2016;Sinha, 2016;Opoku & Nguah, 2015;Akpan, 2014;Mathibe Neke & Matupa, 2013;Yisma,2013;Hasan, 2017;Fatouh & Ramadan, 2015;Suchika et al, 2014;Mandiwa & Zamawe, 2017;Nwaneri et al, 2017;Bedwell, Levin, Pett, & Lavender,2017;Zelellw, 2016;Okokon et al, 2014;Pusparinda, 2015;Markos & Bogale, 2015). used and managed properly, Thus it is necessary to develop the tool (Ashish, Wrammert, Clark, Ewald, & Malqvist, 2016).…”
Section: Introductionmentioning
confidence: 99%